Multi-Dimensional Urban Sprawl in Europe: a Self-Organizing Map Approach - Daniel Arribas-Bel; Peter Nijkamp; Henk Scholten (European Regional Science Association (ERSA), 2010)
The present paper considers urban sprawl in Europe from a multi- dimensional and exploratory point of view. Several literatures on the topic (mainly from urban economics, but also from other fields such as urban planning or regional science) are reviewed to extract the main dimensions of the phenomenon, which are found to be the following six: connectivity, decentralization, density, scattering, accessibility to open space and land- use mix. Several indicators are defined and calculated to measure them for a representative sample of 209 European cities. The data are presented to the self-organizing map (SOM) algorithm to observe how the different dimensions interact with each other and what is their behaviour. The analysis of the SOM reveals very interesting patterns that could not be unveiled otherwise. The paper also presents results of an exploration on the relation to geographical location and population size, characterizing the cities in terms of their degree and variety of sprawl.
Keywords: C45; R12; R14; 330; Keywords Urban sprawl; self-organizing maps; Europe